Prerequisites for developing technology for forming the movement technique of athletes specializing in practical pistol shooting - Ivchenko , Vitalii; Lytvynenko , Yurii (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. Practical shooting is a relatively young type of shooting sport, which aims to organise shooting exercises within the framework of sports competitions, requiring shooters to implement techniques and methods of fire that best suit different cases of using firearms. Practical shooting, originally formed in the late 60s – early 70s of the XX century in the United States as a separate shooting discipline, by 1976 had acquired the status of an independent international shooting sport under the auspices of the International Practical Shooting Confederation (IPSC), which united 62 countries. At the moment, IPSC unites shooting federations in more than 100 countries, and their number is growing every year. The multidirectional nature of practical shooting determines a significant number of angles of its theoretical and practical aspects in scientific research. The purpose of the study is to theoretically substantiate the prerequisites for the development of technology for the formation of movement technique for athletes specialising in practical pistol shooting in motion. Research methods: theoretical analysis and synthesis of special scientific literature, pedagogical observation, pedagogical experiment, expert evaluation, optoelectronic system of 3D registration and analysis of athlete’s movements “Qualisys”, methods of mathematical statistics. The research involved 10 qualified athletes specialising in practical pistol shooting. Each athlete performed 5 attempts in the ways of movement. The research was conducted in compliance with the requirements of the World Medical Association Declaration of Helsinki “Ethical Principles for Medical Research Involving Human Subjects”. The results. The data obtained confirm that athletes performing shots using different methods of movement try to minimise the negative impact of oscillatory processes on the weapon coming from the lower part of the body as a result of walking. However, according to the results of own research, athletes are able to provide the least impact when performing the “X-shaped” movement. This fact is also confirmed by the smallest fluctuations of the weapon’s sights in the frontal and vertical planes, compared to other methods of movement, which was also shown above in the form of quantitative indicators and visual support to them. Conclusions. The research allowed to establish that, regardless of the method of movement in the knee joints, the highest values of angular displacements were found at the time of placing the leg on the support (the limb per-forming the corresponding action). The value of these angles in the right knee joint at the time of placing the right foot on the support varies from 145.600 (S=4.150) in low to 161.83 (S=4.000) in normal movement. In the left knee joint, at the moment of placing the left foot on the support, the studied index varies from 142.440 (S=3.050) in low to 161.860 (S=3.430) in normal movement. The most similar in the biomechanical structure of movements, where the largest number of statistically insignificant (p>0.05) differences between angular indicators of sportsmen specialising in practical pistol shooting were observed, at different moments in the walking cycle in the trunk-thigh biopair there was a low movement and ski stride, in the hip-foot biopair – linear movement and ski stride, in the shin-foot biopair – ski stride and X-shaped movement, low and X-shaped movement, low movement and ski stride.